PEMBERDAYAAN MASYARAKAT DUSUN MANGGUNG, KENTENG DAN BUYUTAN MELALUI KKN UAD - Sulistyawati, Sulistyawati; Rejeki, Suprapti (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2018)
Background: The hamlets of Manggung, Kenteng and Buyutan are 3 sub-villages which part of Ngalang Village, Gedangsari. The three hamlets have different topography however they are having similar problems, namely human resources and infrastructure. Objective: To overcome this problem UAD Community Service Program carried out several activities with aimed improving the management of related hamlets. Method: Socialization, discussion, training, counseling and practice were used in each KKN activity. Then followed by a monitoring and evaluation. Result: This KKN activity run well with good community participation.